Measuring gender transformative change in the context of food security, nutrition and sustainable agriculture - Cole, Steven M.; Acosta, Mariola (International Institute of Tropical Agriculture, 2023)
There is growing recognition of the significance of gender transformative approaches (GTAs) in promoting lasting change towards gender equality and women’s empowerment. GTAs complement, and diverge from, other gender-aware approaches that focus on addressing the symptoms of gender inequalities, without paying sufficient attention to the structural causes of these inequalities. While GTAs have the potential to address structural causes, there is limited guidance on how to measure gender transformative change. This session will present Guidelines for measuring gender transformative change in the context of food security, nutrition and sustainable agriculture—a joint publication from FAO, IFAD, WFP and the CGIAR GENDER Impact Platform—and will provide a hands-on learning experience for participants. The first part of the session will include the presentation of a framework for measuring gender-transformative change (including key dimensions and spheres of influence), points to consider when developing gender transformative change indicators, and a stepby-step process to develop gender-transformative change indicators. The second part of the session will allow participants to use the framework and process to engage in practical activities related to measuring gender-transformative change, including the development of indicators. Participants will be exposed to key theoretical concepts surrounding gender transformative change and gain valuable insights into the indicator development process. The session is intended for gender researchers, officers and practitioners working in agri-food systems.